Real-world outcomes of vedolizumab therapy in ulcerative colitis and Crohn’s disease at a tertiary referral center - Hoffmann, Peter; Krisam, Johannes; Stremmel, Wolfgang; Gauss, Annika (Digestive diseases, 2019)
Background: Vedolizumab was approved for the therapy of ulcerative colitis and Crohn’s disease in mid-2014. Real-world treatment data are necessary for a balanced assessment of its position among other therapeutic options. Summary: Patients with ulcerative colitis or Crohn’s disease, initiating vedolizumab therapy at the outpatient clinic for inflammatory bowel diseases at the University Hospital Heidelberg between June 1, 2014 and August 31, 2016, were recruited based on electronic medical records. The primary study endpoint was response at week 30, while the secondary endpoints were the need for surgery and discontinuation of therapy due to inadequate response, or adverse events. Twenty-five patients with ulcerative colitis (40% anti-tumor necrosis factor α [TNFα] naive) and 28 patients with Crohn’s disease (10.7% anti-TNFα naive, 53.6% having undergone at least one intestinal surgery) were enrolled. Among the ulcerative colitis patients, 20% achieved remission, 32% partial response, and 48% were non-responders to vedolizumab. In Crohn’s disease, 14.3% of the patients achieved remission, 46.4% partial response, and 39.4% were non-responders. Two patients discontinued vedolizumab therapy due to suspected side effects. Key Message: In a relatively treatment-refractory cohort of inflammatory bowel disease patients, vedolizumab was efficacious in achieving response. However, the majority of the patients were not satisfactorily treated, as they did not reach remission.